2018
DOI: 10.1088/1361-6463/aad94c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hot phonon effect on electronic transport in monolayer silicene

Abstract: The hot phonon effect is a non-equilibrium phenomenon that has an important role in highfield electronic transport in two-dimensional electron gases and in 2D materials like graphene. In this work, the influence of this effect on the electronic transport properties of silicene is investigated by means on an ensemble Monte Carlo simulator that accounts self-consistently for the out-of-equilibrium phonon population and the scattering events under high electric field conditions. In this way, the observed reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…While considering the hot phonon effect, τ p = 0, 1 and 5 ps are chosen for illustration for all the optical phonons and intervalley acoustic phonons. We note that the phonon relaxation times τ p are found to be different for different branches and are in the range 1-1.5 ps except for LA and ZO phonon modes at K point for which τ p = 2.5 and 5.0 ps, respectively [36].…”
Section: Resultsmentioning
confidence: 75%
“…While considering the hot phonon effect, τ p = 0, 1 and 5 ps are chosen for illustration for all the optical phonons and intervalley acoustic phonons. We note that the phonon relaxation times τ p are found to be different for different branches and are in the range 1-1.5 ps except for LA and ZO phonon modes at K point for which τ p = 2.5 and 5.0 ps, respectively [36].…”
Section: Resultsmentioning
confidence: 75%
“…It is expected that for still larger n s (> 10n 0 ), the reduction in P op may be larger, because large n s increases hot phonon number and thereby enhancing their reabsorption. Rengel and co-workers [36] have shown that the hot phonon effect has less impact on drift velocity in silicene than in graphene. In Fig.…”
Section: A Power Loss Due To Intrinsic Intravalley and Intervalley Ac...mentioning
confidence: 99%
“…The results presented in this work have been obtained by means of an in-house EMC simulator. The simulator was successfully tested in the past for different 2D materials such as graphene [26], silicene [27], and various TMDs [28,29]. The transport model features a multi-band, multi-valley band structure.…”
Section: Emc Modelmentioning
confidence: 99%